Kesepakatan Wanprestasi dan Pernyataan Sukarela dalam Putusan MK No. 18/PUU-XVII/2019 terhadap Kekuatan Eksekusi Jaminan Fidusia - Kurniawan, Deni Hendri; Badriyah, Siti Malikhatun (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to find out practical steps to determine the default agreement and voluntary statement in Constitutional Court Decision No.18/PUU-XVII/2019 regarding the executorial power of fiduciary guarantees. This type of research is normative legal with a statutory approach and a conceptual approach. Research data was found by means of library research studying primary, secondary and tertiary legal materials. The results of this research indicate that financing companies in carrying out their business activities using credit distribution mechanisms are required to enter into financing agreements with articles of default (stipulations for debtors in default); This means that the finance company as the creditor must include a default article with content material that is required by POJK 35/2018 and in determining whether the customer is in default, they must be given a warning letter with information that all guarantees legal certainty or is in accordance with the existing default agreement; and the form of a voluntary statement to create legal certainty as intended by Constitutional Court Decision No.18/PUU-XVII/2019 is that apart from the voluntary clause contained in the contents of the financing agreement, it can be made with a special statement letter stating that you voluntarily hand over fiduciary guarantees when a default has occurred. previously agreed.